Synthesis And Evaluation Of Some Newer Indole Derivatives As Anticonvulsant Agents - Kumar, Anil (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTA new series of 3-(4-substituted phenyl)-3-(substituted phenyl aminomethylene)-2,3-dihydrobenzoxazepin/benzothiazepin-2-yl)-2,5-disubstituted indoles (13-36) were synthesized for anticonvulsant activity. Compound (30) found to be most potent compound of this series. All compounds were screened in vivo for their anticonvulsant activity and acute toxicity studies. The structural assignment of these compounds has been made on the basis of elemental analysis, IR and 1H-NMR data